Sebocytes contribute to skin inflammation by promoting the differentiation of T helper 17 cells. (29th March 2018) - Mattii, M.; Lovászi, M.; Garzorz, N.; Atenhan, A.; Quaranta, M.; Lauffer, F.; Konstantinow, A.; Küpper, M.; Zouboulis, C.C.; Kemeny, L.; Eyerich, K.; Schmidt‐Weber, C.B.; et al.
Summary: The main function of cells in the skin called sebocytes is considered to be the production of lipids (oils) to moisturize the skin. It used to be thought that they were bystander cells during skin inflammation with no impact on the body's immune response, meaning they did not help the body to fight off signs of infection on inflammation. However, it recently became apparent that sebocytes do in fact respond to signs of inflammation (proinflammatory stimuli) as well as the presence of bacteria, and they release tiny protein molecules called chemokines and cytokines which play a role in inflammation. This discovery prompted scientists from Germany and Hungary to examine samples of skin with acne and skin without acne, to see if sebocytes also have any influence over white blood cells of the immune system (immune cells). The researchers found that sebocytes do indeed participate in inflammatory processes in the skin by recruiting and communicating with immune cells, and this interaction leads to the generation of Th17 cells. Further studies have to clarify whether this relationship between sebocytes and Th17 cells helps the immune system or, on the contrary, contributes to the development not only of acne, but also of several inflammatory skin diseases. Abstract : Linked Article:  Mattii et al. Br J Dermatol 2018;178 :722–730